2011
DOI: 10.1177/1757177410389627
|View full text |Cite
|
Sign up to set email alerts
|

Covering more territory to fight resistance: considering nurses’ role in antimicrobial stewardship

Abstract: The potential contribution nurses can make to the management of antimicrobials within an inpatient setting could impact on the development of antimicrobial resistance (AMR) and healthcare associated infections (HCAIs). Current initiatives promoting prudent antimicrobial prescribing and management have generally failed to include nurses, which subsequently limits the extent to which these strategies can improve patient outcomes. For antimicrobial stewardship (AS) programmes to be successful, a sustained and sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 42 publications
3
91
0
11
Order By: Relevance
“…However, other healthcare workers also play an important role in AMS at the individual patient level including junior and senior doctors, nurses, non-medical prescribers and ward pharmacists. [36][37][38][39][40][41] Inclusion of these professional groups in user-testing at the design stage of EPMA implementation is likely to be critical to the success of the proposed software features. Future surveys focussing on front-line prescribers and medication administrators are critical.…”
Section: Discussionmentioning
confidence: 99%
“…However, other healthcare workers also play an important role in AMS at the individual patient level including junior and senior doctors, nurses, non-medical prescribers and ward pharmacists. [36][37][38][39][40][41] Inclusion of these professional groups in user-testing at the design stage of EPMA implementation is likely to be critical to the success of the proposed software features. Future surveys focussing on front-line prescribers and medication administrators are critical.…”
Section: Discussionmentioning
confidence: 99%
“…The residual volume results found still raise concerns about antibiotic management in the institution under study. It is worth mentioning that drug management programs have been implemented throughout many European hospitals, but nurse involvement has been limited even though it is described as being multidisciplinary in approach, which is due to the workload and high turnover of nursing staff (11) . Medication management depends on correct medical prescription, dispensing, preparation and administration aimed at the rational use of medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Losses should be continuously avoided under penalty of being harmful to collective health and also to public funds (12) . As the most consistent bedside care providers, nurses have an ideal position to improve antibiotic management through multidisciplinary collaboration, optimizing treatment, monitoring and administration, while improving pediatric patient safety and quality of care (11) . The lack of parenteral drugs in adequate presentation for pediatrics represents a worldwide problem, constituting one of the factors that most contributes to the reuse of these medicines and also to increased care costs (13)(14) .…”
Section: Discussionmentioning
confidence: 99%
“…insulin, and ensuring timely and correct administration of antimicrobials. [7] A study conducted in 33 Netcare hospitals found that pharmacists and nurses can collectively improve the timeous administration of antibiotics. [8] Among other things, the study involved institutional system changes and the creation of awareness of administration priority, changing perceptions on waiting times for fixed dosing schedules, and adding commonly prescribed antibiotics to ward stock to prevent delays in administration.…”
Section: The Current Situationmentioning
confidence: 99%